Bairisch-österreichische Dialektliteratur vor 1800 Eine andere Literaturgeschichte - Neuhuber, Christian (2019)
These days, it is commonly forgotten that Bavarian-Austrian dialect art flourished in elite culture and even more in popular counterculture before 1800. The book makes the amazing variety of forms and modes of operation visible again. In eight chapters, the most important, predominantly unedited texts and their authors are presented, contextualized, and related to current research fields using an interdisciplinary approach.